Determinan Kinerja Karyawan: Faktor Gaya Kepemimpinan dan Disiplin Karyawan - Ida Nirwana; Seflidiana Roza; Habib Maulid (JURNAL ADMINISTRASI KANTOR, 2024)
This research aims to determine: Determinants of Employee Performance: Leadership Style and Employee Discipline Factors. The type of research used is quantitative descriptive research. The data used is primary data. The research results show that: (1) leadership style has a significant effect on the performance of employees of Perum Bulog Kota Solok, as evidenced by a value greater than ttable and a significant probability value of (0.002 < 0.05); (2) discipline has a significant effect on the performance of employees of Perum Bulog Kota Solok, as evidenced by a value greater than ttable at a significant level of 5% and a significant probability value of (0.000 < 0.05); (3) Leadership style and discipline have a significant and simultaneous influence on the dependent variable of employee performance with Fcount of 23.416 > 3.35, and a coefficient of determination test of 63.4% while the remaining 36.6% is explained by other variables. not included in this research such as workload, job satisfaction, cooperation and others. Keywords: Employee Performance, Leadership Style, Discipline